2007
DOI: 10.1016/j.mce.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between estrogen-related receptor alpha (ERRα) and gamma (ERRγ) on the regulation of ERRα gene expression

Abstract: Estrogen-related receptor α (ERRα) modulates estrogen receptor (ER)-mediated activity and is participating in the energy homeostasis by regulation of downstream target genes. The ERRα gene itself is proposed to be regulated by peroxisome proliferator-activated receptor γ coactivator (PGC-1α) through an autoregulatory loop under physiological stimulation. We have previously shown that the close family member ERRγ is a positive regulator of ERRα gene expression. ERRα and ERRγ are coexpressed in metabolically act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 65 publications
2
44
0
Order By: Relevance
“…Furthermore, it has been suggested that ERRg activates the DAX-1 promoter, which in turn inhibits ERRg through coactivator competition (an autoregulatory loop). Moreover, it was demonstrated that ERRg stimulates ERRa gene expression whereas its own gene product represses ERRg's activity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that ERRg activates the DAX-1 promoter, which in turn inhibits ERRg through coactivator competition (an autoregulatory loop). Moreover, it was demonstrated that ERRg stimulates ERRa gene expression whereas its own gene product represses ERRg's activity [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, ERR␣ did not affect the FSK-stimulated DNA binding ability of ERR␥ on Pck1 ERREs. Similarly, it has been shown that ERR␣ can inhibit ERR␥ transcriptional activity without affecting the DNA binding ability of ERR␥ and suggested that a mechanism for ERR␣ repression is the heterodimerization between the ERRs as evidenced by the reports showing that heterodimerization between ERR␣ and ERR␥ inhibits transactivation of each other, whereas homodimerization is needed for their transcriptional activity (32,48,49). On the other hand, their functions in terms of transcriptional regulation of each ERR for downstream targets are more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…under Fasting-It has been reported that hepatic expression of ERR␥ rhythmically oscillates in the daily light/dark cycle and is induced during fasting (21,32), suggesting that it could be regulated by nutritional status. Because glucagon stimulates hepatic glucose production mainly through the cAMP signaling pathway under fasting (33), we first investigated whether ERR␥ expression is induced by the adenylate cyclase activator forskolin (FSK) in AML12 cells and rat primary hepatocytes.…”
Section: Hepatic Err␥ Expression Is Induced By Camp Signalingmentioning
confidence: 99%
“…ERR␣ and ERR␥ are known MHRE-binding proteins (63,66) and therefore candidate components of the MHRE binding complex detected in MCF-7 NPEs. The ER␣ could potentially be tethered to the MHRE and co-occupy the region with DNAbound ERRs (29) or, alternatively, may be tethered to AP1 (67)(68)(69) or SP1 (7,70) complexes bound to their consensus binding sites located upstream as well as within the MHRE nucleosome.…”
Section: Estrogen Induces Err␣ Expression In Mcf-7 Cells Via An Er␣-mmentioning
confidence: 99%